Effectiveness of Intra-articular Steroid Injection in Treatment of Idiopathic Frozen Shoulder Followed by Physiotherapy and Home Exercise Program. - Sah, Shambhu; Karn, Shivam; Sigdel, Deepak; Dahal, Mukunda; Kathet, Ragin; Yadav, Roshan; Adhikari, Anurag Raj (Birat Journal of Health Sciences, 2019)
Introduction: Idiopathic frozen shoulder (IFS) is a common chronic and disabling condition of shoulder pain characterized by progressive loss of active and passive range of motion (ROM) with unclear pathogenesis. The ideal treatment protocol is still controversial but commonly used treatment includes single agent or combination of oral non-steroid anti- inflammatory drugs (NSAIDS), oral steroids, intra-articular steroid injection and physiotherapy.Objective: The objective of this study was to evaluate the effectiveness of intra-articular methylprednisolone injection for pain and ROM in patients suffering from idiopathic frozen shoulder who did not respond to oral NSAIDS with or without oral steroid.Methodology: A total of 70 patients suffering from IFS were enrolled in this cross sectional study from May 2017–October 2018 from outpatient department of orthopaedic and physiotherapy of Koshi Zonal Hospital. All the patients underwent treatment protocol that comprised of Intra-articular steroid injection followed by five days of oral NSAIDS along with five days regime of physical therapy at the physiotherapy centre, followed by home exercise program. Each patient was followed up at every two weeks interval from intra-articular injection till 6th week. Each patient was evaluated for range of motion (ROM), Numerical Pain Rating Scale (NPRS) and Shoulder Pain and Disability Index (SPADI) before the treatment protocol and at every follow up visit. Data was analyzed using Microsoft Excel Program.Results: All patients enrolled for the study had satisfactory response. The mean age of the patient was 51.8 years (range 40-65 years). The mean age of the 26 male patients was 54 years (range 45-65), whereas the mean age of 44 female patients was 50.5 years (range 45-60). Mean duration of illness was 26.5 weeks (range 18-32 weeks), SPADI before medication was 83.14, at 2nd week was 50.92, at 4th week was 38.63 and at 6th week was 27.22.Conclusion: Combination of intra-articular methylprednisolone injection, physiotherapy and home exercise program is effective in IFS for rapid improvement in pain and ROM.